Забезпечення інноваційного розвитку гірничорудних підприємств на основі ресурсної концепції - Темченко, О. А.; Петрук, М. В. (Видавництво Львівської політехніки, 2015)
Досліджено застосування ресурсної концепції як засобу забезпечення інноваційного розвитку гірничорудних підприємств. Особливу увагу зосереджено на специфічних проблемах у діяльності вітчизняних гірничорудних підприємств, обґрунтуванні необхідності реалізації стратегії екологозбалансованого природокористування, а також формуванні системи пріоритетних факторів забезпечення інноваційного розвитку в складних умовах господарювання. The article studies the issue of introducing strategic management taking into account the need to ensure innovative development of domestic mining enterprises. In conditions of difficult economic and financial environment, globalization of economic activity and tough international competition further innovative development has special significance to ensure long-term competitive advantages. Studying this issue the attention is focused on identifying specific problems in the activities of domestic mining enterprises and forming the system of the most important factors for their innovative development. The object of the research is the mining companies that have unique features of the activities, involving the use of various types of resources, and in the first place, natural resources. Considering specifics of such enterprises, the primary objectives are to assess the efficiency of using mineral resources, with implementation of the strategy of ecological and sustainable natural resources management. Scientific novelty consists in forming the system of indicators in three priority components (economy, ecology and social environment), the definition of which will give a full assessment of opportunities to improve the efficiency of mining and prospects of sustainable innovative development of the mining enterprises taking into account the key factors of its components. A significant achievement is the development and justification of scientific and methodological approaches to the formation of organizational and economic bases of increase of efficiency of production economic activity and sustainable and innovative development of the mining enterprises on the basis of the resource concept. Scientific results should be used at the enterprises of mining and metallurgical complex of Ukraine in the context of improving the efficiency of their production and economic activity and sustainable and innovative development with the development of an appropriate mechanism and sustainable strengthening their competitive position on the modern market of iron ore materials.
Providing innovate development of mining enterprises on the basis of resource concept
Keywords: сталий розвиток; ресурсна концепція; мінерально-сировинні ресурси; інноваційний розвиток; sustainable development; resource concept; mineral resources; innovative development